2017
DOI: 10.1007/s00262-017-2086-8
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between TNF-α and IFN-γ signaling in induction of B7-H1 expression in hepatocellular carcinoma cells

Abstract: Clinical benefit from immunotherapy of B7-H1/PD-1 checkpoint blockade indicates that it is important to understand the regulatory mechanism of B7-H1 expression in cancer cells. As an adaptive response to the endogenous antitumor immunity, B7-H1 expression is up-regulated in HCC cells. B7-H1 expression is induced mainly by IFN-γ released from tumor-infiltrating T cells in HCC. In addition, HCC is a prototype of inflammation-related cancer and TNF-α is a critical component of inflammatory microenvironment of HCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 42 publications
2
50
0
Order By: Relevance
“…Virus-specific IFN-γ secreting CD8+ and CD4+ T cells are believed to play a key role on HBV clearance and control [16-18]. However, both type I/II interferons were shown to promote PD-L1 expression in hepatocytes, which may induce T cell apoptosis [19-21]. Therefore, further elucidating the mechanism of hepatic PD-L1 expression induced by IFN-α/γ and its role in T cell response will shed light on the underlying mechanism of antiviral T cell tolerance and the unique immunological properties of liver.…”
Section: Introductionmentioning
confidence: 99%
“…Virus-specific IFN-γ secreting CD8+ and CD4+ T cells are believed to play a key role on HBV clearance and control [16-18]. However, both type I/II interferons were shown to promote PD-L1 expression in hepatocytes, which may induce T cell apoptosis [19-21]. Therefore, further elucidating the mechanism of hepatic PD-L1 expression induced by IFN-α/γ and its role in T cell response will shed light on the underlying mechanism of antiviral T cell tolerance and the unique immunological properties of liver.…”
Section: Introductionmentioning
confidence: 99%
“…3A and Table ). Previous studies [30] have confirmed that the IFN‐γ pathway is one of the key pathways to induce PD‐L1 expression. TGF‐β plays an important role in promoting tumor immune escape and immunotherapy resistance [24,31].…”
Section: Resultsmentioning
confidence: 86%
“…TNF-α is reported to synergistically act with IFN-γ to induce PD-L1 expression at both mRNA and protein levels. IFN-γ enhances the resistance of the adaptive immune response by PD-L1 induction in hepatocellular carcinoma cells which upregulate the expression of IFN-γ receptors [41]. PD-L1 is expressed not only in all hematopoietic cells but also in many non-hematopoietic cell types, such as endothelial and epithelial cells [42,43].…”
Section: Immune Checkpoint Inhibitors and Reagents For Side-effect Rementioning
confidence: 99%